“Implementación de una máquina pulverizadora de neumáticos fuera de uso” - Quintana Reyes, Javier Alejandro (2021)
This research project is based on the "Implementation of an out-of-use tire spray machine" using scientific references as a bibliographic background on rubber spraying, this process has various applicability in the industrial field; park cobblestones, shoe sole, gym floors, asphalt cement, synthetic courts. The spray machine was developed in favor of students of the Engineering In Electromechanics Career of the Technical University of Cotopaxi Extension La Maná, for the construction of the prototype machine, the modeling of the prototype was carried out applying Autodesk Inventor software which complies with the parameters of modeling and analysis of the elements, using the von Mises method and finite elements applied in the elements of the machine , in the construction of rotary impact plates (Knives) Steel 705 AISI 4340 was used to provide better quality when spraying crushed rubber; 52 Toothed grinding parts that will be welded around the spray cylinder will help spray the rubber once it is entered through the hopper.